Os usos da palavra golpe como repertório linguístico do processo de impedimento de 2016 no jornal O Estado de S. Paulo - Ramos, Maurício Del Buono (2019)
The objective of this paper is to identify the uses of the term coup as a discursive repertoire in the impeachment of Dilma Rousseff in the O Estado de S. Paulo newspaper. The argument of this paper is derived from the historiographic importance of the word coup in Brazil´s politics and its complexity in the Portuguese language. The theoretical approach is based on Constructionism studied in the Núcleo de EStudos e Pesquisas sobre Práticas Discursivas no Cotidiano: Direitos, Riscos e Saúde (NUPRAD), PUC-SP. The three main authors and their respective publications are Mary Jane Spink “Linguagem e Produção de Sentidos no Cotidiano”; Mikhail Bakhtin “Speech Genres” and John B. Thompson, “Ideology and modern culture”. The specific objectives are: to analyze the editorial proposal of the newspaper, map all articles related to the impeachment that appears on the main page and analyze all articles containing the word coup in its title or body. The analyses were done through discourse legitimation aspects that derive into two thematic axes